Superomedial pedicle reduction mammaplasty with and without drains: a comparative analysis - Derek G Liang; Varun Harish; Steven L Merten (Australasian Journal of Plastic Surgery, 2019)
**Background**: Postoperative suction drainage has historically been a routine part of care following reduction mammaplasty surgery. Purported benefits are a reduction in complications such as haematoma, seroma, delayed wound healing and loss of nipple or areola. The aim of this study is to compare the complication profile of breast reduction surgery patients who had received postoperative drains and those who had not. **Methods**: A retrospective analysis was conducted of consecutive reduction mammaplasties performed by experienced surgeon and co-author Dr Merten. A total of 172 patients over the period January 2011 to June 2017 were identified. Statistical analysis with regression modelling was used to compare the complication profile between patients who had and had not received postoperative drainage. **Results**: Patients were evenly divided between the ‘drained’ (n = 86) and ‘drainless’ (n = 86) cohorts. There was no significant difference in age, smoking status and diabetic status between the two groups (_p_ > 0.05). Mean body mass index (BMI) was significantly higher in the drained group (29.0 compared to 25.7 in the drainless cohort, _p_ < 0.05). Patients in the drained group also had a significantly higher breast weight reduction (660 g compared to 536 g, _p_< 0.05). There was significantly more vertical skin resection patterns in the drained group (n = 25 or 29.1%) as compared to the drainless group (n = 8 or 9.3%) (with _p_ = 0.001). Using multivariate logistic regression, drains resulted in a slightly lower risk for complications but this difference was not statistically significant (OR 0.84; 95% CI = 0.39-1.81; _p_ = 0.66). However, BMI was strongly associated with complications (_p_ = 0.007). **Conclusions**: Our results support the contention that routine postoperative drain insertion in reduction mammaplasty does not significantly reduce complications irrespective of the patient’s BMI, breast tissue reduction weight, use of liposuction or skin resection pattern.